Apresiasi terhadap Karya Arsitektur Jengki di Kota Makassar - Jamaluddin, Husnirrahman; Wiranata, Tri Amartha; Edar, Ahmad Nadhil (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2025)
Houses with jengki architectural style in Makassar City and even in other cities in Indonesia are already threatened to disappear from sight. Rumah bergaya arsitektur jengki ini sudah sangat sulit ditemukan, padahal gaya arsitektur ini terbilang unik dan kreatif. It is very interesting to discuss the characteristics of this jengki architecture, so on this occasion through direct observation and examination, the author will attempt to critique this architectural style. For that reason, the author will attempt to appreciate this jengki architectural work, as it is part of the architectural history, especially in Indonesia